Philosophy of education : major themes in the analytical tradition V. 4 : Problems of educational content and practices (London ; New York : Routledge, 1998)
Controversial areas of educational content. Educational practices. Controversial issues of curriculum development.
Keywords: Education; Critical pedagogy; Philosophy; Education -- Philosophy; Critical pedagogy -- Philosophy; Educational sociology